From a systems theory of sociology to modeling the onset and evolution of criminality - Bellomo, Nicola; Colasuonno, Francesca; Knopoff, Damián Alejandro; Soler, Juan (2022)
Fil: Bellomo, Nicola. Universidad del Rey Abdulaziz. Facultad de Ciencias. Departamento de Matemáticas; Arabia Saudita.